A method for enhancing the surface wear resistance of a low-carbon martensitic stainless steel component and a component
Patent Information
- Application Number
- CN202510143812.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-02-10
AI Technical Summary
值得注意的是,由于水电站机组结构件需要长期承受水流冲击导致的疲劳载荷,因此单纯提高构件表面的硬度难以保证构件在长期服役过程中不剥落,所以在提高其表面耐磨性的同时,还不能显著丧失其韧性;文献“CN118497740A”虽然公开了提高不锈钢表面性能的方法,但并非解决低碳马氏体不锈钢基体性能的问题,即并非04Cr13N i5Mo不锈钢基体性能的问题,无法达到“增加表面耐磨性的同时,还不会显著丧失基体的韧性”这一要求
[0023] 1. This invention involves cladding wear-resistant alloy powder onto a stainless steel substrate. Due to the similar C and Cr contents of the stainless steel substrate and the wear-resistant alloy powder, they have good compatibility, thereby ensuring the bonding strength between the stainless steel substrate and the cladding layer and the toughness of the component formed after bonding.
Smart Images

Figure CN119824411B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wear-resistant protection of metal component surfaces, and in particular to a method and component for enhancing the wear resistance of low-carbon martensitic stainless steel components. Background Technology
[0002] Components operating under high-speed airflow or water flow for extended periods typically withstand cyclic impact loads, thus facing a significant risk of wear failure. While using high-strength, high-hardness, and high-toughness high-quality alloy materials can improve the wear resistance of components, this will greatly increase raw material costs and also lead to higher maintenance costs in the later stages of the component's service life.
[0003] Low-carbon martensitic stainless steel is widely used in structural components in the hydropower industry due to its excellent corrosion resistance and high fatigue strength. These components are subjected to long-term water flow impact loads, and their surfaces are typically worn by the constant scraping of hard silt and sand in the water, especially components operating in waters with high sand content, where wear is more severe. Furthermore, with the development of high-head, large-capacity impact turbine units, the wear conditions experienced by components have become increasingly demanding, rendering the original surface wear resistance insufficient. Therefore, breakthroughs must be sought to develop methods to enhance the surface wear resistance of low-carbon martensitic stainless steel components.
[0004] Heterogeneous material reinforcement is a reliable method to improve the surface wear resistance of components. By metallurgically combining materials with different properties, reinforced components with different property combinations can be prepared. At present, technologies such as supersonic spraying, surface chrome plating, and thermal spraying are used to improve the surface hardness of components, thereby improving their surface wear resistance. For example, Chinese patent CN118497740A discloses "A solution-treated and aged anti-cavitation nickel-titanium alloy coating and its preparation method," which aims to solve the problem that the anti-cavitation performance of laser-clad anti-cavitation NiTi coatings on stainless steel substrates is significantly lower than that of superelastic NiTi alloys. It is worth noting that, since the structural components of hydropower station units need to withstand fatigue loads caused by water flow impact for a long time, simply increasing the surface hardness of the components is not enough to ensure that the components do not peel off during long-term service. Therefore, while improving the surface wear resistance, the toughness should not be significantly lost. Although the literature "CN118497740A" discloses a method to improve the surface properties of stainless steel, it does not solve the problem of the matrix properties of low-carbon martensitic stainless steel, that is, it is not a problem of the matrix properties of 04Cr13Ni5Mo stainless steel. Therefore, it cannot achieve the requirement of "increasing the surface wear resistance without significantly losing the toughness of the matrix".
[0005] Therefore, it is necessary to study a new technical solution. Summary of the Invention
[0006] The purpose of this invention is to provide a method and component for enhancing the surface wear resistance of low-carbon martensitic stainless steel components, thereby improving the surface wear resistance of low-carbon martensitic stainless steel components while retaining the strength and toughness of the matrix.
[0007] The technical solution adopted in this invention is as follows: A method for enhancing the surface wear resistance of low-carbon martensitic stainless steel components, targeting a stainless steel substrate, includes the following steps:
[0008] S1: Clean the surface of the stainless steel substrate and dry the wear-resistant alloy powder to be clad;
[0009] S2: A wear-resistant alloy powder is clad onto a stainless steel substrate using laser cladding to obtain a clad component; the wear-resistant alloy powder and the stainless steel substrate have similar C and Cr contents, that is, the C and Cr contents of the wear-resistant alloy powder are 60%-130% of those of the stainless steel substrate.
[0010] S3: The obtained clad component is aged at a temperature below the initial temperature of austenite transformation (Ac1).
[0011] For ease of explanation, the component that combines the stainless steel substrate with the cladding layer is referred to as a component.
[0012] Furthermore, the stainless steel matrix is a 04Cr13Ni5Mo matrix.
[0013] Furthermore, in step S1, when cleaning the surface of the stainless steel substrate, the oil stains are wiped off with alcohol to ensure that the surface of the stainless steel substrate is clean.
[0014] Further, in step S1, the wear-resistant alloy powder comprises the following elements in mass percentage:
[0015] C (0-0.03%); Cr (11.5%-14.0%); Ni (7.5%-9.5%); Cu (1.0%-2.5%); Nb (0.3%-0.6%); Ti (0.5%-1.4%); Mo (0.1%-0.3%); Mn (0.1%-0.3%); Si (0.1%-0.3%); Al (0.1%-0.3%); P (0-0.04%); S (0-0.03%); O (0-0.04%); N (0-0.04%); the remainder being Fe and unavoidable impurity elements.
[0016] Furthermore, in step S2, the thickness of the cladding layer on the stainless steel substrate is between 2mm and 5mm. Within this thickness range, on the one hand, the wear resistance and strength requirements can be met; on the other hand, the possibility of crack propagation can be reduced, thereby significantly improving the toughness of the component itself. At the same time, the manufacturing defects of the component, such as cracks and irregular weld shapes, are significantly reduced. Therefore, when designing the thickness of the reinforcing layer, the thickness of the substrate material should be comprehensively considered, and the thickness of the reinforcing layer should be increased as much as possible to obtain better wear resistance while ensuring that the toughness of the component meets the requirements.
[0017] Furthermore, multiple laser cladding processes are employed to achieve the required cladding thickness, ensuring the bonding strength of the cladding layer and improving its bonding stability.
[0018] Furthermore, the particle size of the wear-resistant alloy powder is 150-300 mesh.
[0019] Furthermore, in step S3, during the aging process, the temperature is 460℃~480℃, the time is 3h~4h, and the cooling method is air cooling.
[0020] A wear-resistant low-carbon martensitic stainless steel component is prepared by the method for enhancing the wear resistance of the surface of the low-carbon martensitic stainless steel component, comprising a base layer and a cladding layer, wherein the cladding layer is located on the surface of the base layer.
[0021] Furthermore, the thickness of the cladding layer is between 2mm and 5mm; and / or the material of the base layer is 04Cr13Ni5Mo.
[0022] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0023] 1. This invention involves cladding wear-resistant alloy powder onto a stainless steel substrate. Due to the similar C and Cr contents of the stainless steel substrate and the wear-resistant alloy powder, they have good compatibility, thereby ensuring the bonding strength between the stainless steel substrate and the cladding layer and the toughness of the component formed after bonding.
[0024] 2. The wear-resistant alloy powder of the present invention contains reinforcing alloying elements such as Ti and Nb, thereby improving the material hardness and wear resistance; in addition, the Cu, Al, Ni and other elements contained therein can easily form nanoparticle reinforcing phases, thereby further improving the strength and surface wear resistance of the components.
[0025] 3. This invention strengthens the stainless steel by laser cladding followed by aging treatment. Since the stainless steel substrate is made of low-carbon martensitic stainless steel, its microstructure does not change significantly during heat treatment, so its strength and toughness do not change significantly. In addition, after aging treatment, nano-scale precipitated strengthening phases of Al2Cu and Ni3Al will precipitate inside the cladding layer, which can significantly increase the surface hardness and wear resistance of the component. Attached Figure Description
[0026] The present invention will be described by way of example and with reference to the accompanying drawings, wherein:
[0027] Figure 1 SEM image of the cladding powder;
[0028] Figure 2 Image of a multi-layer, multi-pass laser cladding plate;
[0029] Figure 3 Image showing the PT flaw detection effect of a multi-layer, multi-channel laser cladding flat panel;
[0030] Figure 4 Metallographic structure of the laser cladding layer;
[0031] Figure 5 This is a SEM image of the laser cladding layer.
[0032] Figure 6 This indicates the sampling location for the hardness test sample;
[0033] Figure 7 These are the hardness test results for the laser cladding sample;
[0034] Figure 8 This refers to the bending performance test process;
[0035] Figure 9 This is a test sample for the bending performance of laser cladding. Detailed Implementation
[0036] In the description of this specification, it should be noted that if terms such as "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," or "outer" appear to indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship commonly used when the product is in use, they are only for the convenience of describing this specification and simplifying the description, and do not indicate or imply that the device or component referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this specification.
[0037] Furthermore, the use of terms such as "horizontal" or "vertical" in this specification does not imply that the component must be absolutely horizontal or suspended, but rather that it can be slightly tilted. For example, "horizontal" simply means that its direction is more horizontal relative to "vertical," and does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0038] In the description of this specification, it should also be noted that, unless otherwise expressly specified and limited, the terms “set up,” “install,” “connect,” and “link” should be interpreted broadly. For example, a link can be a fixed link, a detachable link, or an integral link; it can be a mechanical link or an electrical link; it can be a direct link or an indirect link through an intermediate medium; it can be a connection within two components.
[0039] Example 1
[0040] A method for enhancing the surface wear resistance of low-carbon martensitic stainless steel components, targeting a stainless steel matrix of 04Cr13Ni5Mo, includes the following steps:
[0041] S1: Clean the stainless steel substrate surface with alcohol to remove oil stains; dry the wear-resistant alloy powder to be coated; the particle size of the wear-resistant alloy powder is 150-300 mesh; the composition of the wear-resistant alloy powder includes the following elements by mass percentage:
[0042] C (0-0.03%); Cr (11.5%-14.0%); Ni (7.5%-9.5%); Cu (1.0%-2.5%); Nb (0.3%-0.6%); Ti (0.5%-1.4%); Mo (0.1%-0.3%); Mn (0.1%-0.3%); Si (0.1%-0.3%); Al (0.1%-0.3%); P (0-0.04%); S (0-0.03%); O (0-0.04%); N (0-0.04%); the remainder being Fe and unavoidable impurities; preferably, C: 0.02%; Cr: 12.5%; Ni: 8.6%; Cu: 1.5%; Nb: 0.5%; Ti: 0.0%; Mo: 0.02%; Mn: 0.0%; Cu: 0.0%; Cu: 0.0%; Nb: 0.0%; Ti: 0.0%; Ni ... i: 0.8%; Mo: 0.23%; Mn: 0.24%; Si: 0.27%; Al: 0.15%; P: 0.009%; S: 0.005%; O: 0.023%; N: 0.007%, where P, S, and N are impurity elements, and the remainder is Fe.
[0043] S2: A wear-resistant alloy powder is clad onto a stainless steel substrate using laser cladding to obtain a clad component; the wear-resistant alloy powder and the stainless steel substrate have similar C and Cr contents; the thickness of the cladding layer on the stainless steel substrate is between 2mm and 5mm, and the cladding layer is formed by cladding the wear-resistant alloy powder.
[0044] In this embodiment, multiple laser cladding processes are used to achieve the desired cladding thickness.
[0045] S3: The obtained clad component is aged at a temperature lower than the initial temperature of austenite transformation (Ac1). During aging, the temperature is 460℃~480℃ and the time is 3h~4h. The cooling method is air cooling.
[0046] Example 2
[0047] A wear-resistant low-carbon martensitic stainless steel component is prepared using the method for enhancing the surface wear resistance of low-carbon martensitic stainless steel components described in Example 1. It includes a base layer and a cladding layer, wherein the cladding layer is located on the surface of the base layer; the thickness of the cladding layer is between 2 mm and 5 mm; and the material of the base layer is 04Cr13Ni5Mo.
[0048] Specifically, a multi-layer cladding experiment was conducted on a 04Cr13Ni5Mo substrate with dimensions of 200mm × 200mm × 40mm (length, width, thickness). The three cladding layers had dimensions of 135mm × 180mm × 4.5mm (length, width, thickness). The experimental steps were as shown in Example 1. The wear-resistant alloy powder was approximately spherical with a particle size of 150-300 mesh. Figure 1 As shown in Table 1.
[0049] Table 1. Process parameters for laser cladding
[0050]
[0051] A physical image of a multi-layer, multi-pass laser cladding plate is shown below. Figure 2 As shown, after the cladding layer cools, PT (Potential Testing) is used to inspect for defects in the cladding layer. Before the inspection, the surface of the cladding layer is milled with a milling machine to check for internal defects. Figure 3 The image shows the surface effect after PT flaw detection. It can be seen that no defects such as cracks or lack of fusion are found inside the large-area cladding layer with multiple layers.
[0052] A cross-sectional sample of the cladding layer (perpendicular to the cladding direction) was taken. A metallographic etchant was prepared using 1.5g copper dichloride + 33ml concentrated hydrochloric acid + 33ml anhydrous ethanol. The etchant was applied to the polished cladding layer sample surface with a cotton swab and wiped for 10 seconds. The microstructure was observed using a metallographic microscope and a scanning electron microscope. The metallographic microstructure of the cladding layer is as follows: Figure 4 As shown in the metallographic image, the internal structure of the cladding layer is dense, without obvious defects such as porosity, lack of fusion, or cracks. The electron microscopy observation results of the cladding layer are as follows: Figure 5As shown in the low-magnification and high-magnification SEM images of the microstructure after etching, the cladding layer is martensitic, and the selected etchant more readily corrodes the grain boundaries. The interface between the cladding layer and the substrate is clearly visible in the SEM images, and no defects are found at the interface. This is due, on the one hand, to the selection of an appropriate cladding process: high-power laser cladding, with sufficiently high energy density, resulting in more significant mixing of elements between the cladding layer and the substrate in the interface region, leading to a good metallurgical bond; on the other hand, the wear-resistant alloy powder and the substrate are both ultra-low carbon martensitic stainless steel, with similar compositions, thus ensuring good interfacial compatibility.
[0053] Furthermore, to demonstrate the performance-enhancing effects of laser cladding and aging treatment on components, mechanical property measurements were performed on components with only laser cladding and those subjected to heat treatment after laser cladding. Details are as follows.
[0054] First, two samples were prepared on a single-pass four-layer laser cladding specimen. One sample underwent solution-aging heat treatment, while the other was not heat-treated. Sampling locations are as follows: Figure 6 As shown. The hardness of the two samples was measured, and the results are as follows. Figure 7 As shown, SA500 represents the sample that underwent laser cladding only, and HT-SA500 represents the sample that underwent heat treatment after laser cladding; the notation is the same below. The hardness curves show that the cladding layer thickness is approximately 3.5 mm, and the average hardness of the cladding layer is 33 HRC. After aging treatment, the hardness increases to 50 HRC, which is 1.5 times the hardness of the untreated cladding layer. In the heat-affected zone, the hardness rapidly decreases, recovering to around 33 HRC, and the depth of the heat-affected zone is approximately 1 mm. The hardness measurement results indicate that after laser cladding and heat treatment, the surface hardness of the component is significantly improved, and correspondingly, its wear resistance is also significantly enhanced.
[0055] According to GB / T 232-2010 "Metallic Materials Bending Test Method", bending tests were conducted on the laser-clad components. The experimental procedure is as follows: Figure 8 As shown in Table 2, the results of the bending test are summarized in Table 2. The specimens after the bending test are as follows: Figure 9 As shown. By comparing (1) and (2), and (3) and (4), it can be seen that the bending performance of the sample is greatly improved after aging treatment.
[0056] Table 2 Summary of Bending Test Parameters and Results
[0057]
[0058] Note: Pure cladding layer refers to bending samples taken entirely from the cladding layer; "cladding layer + substrate" means the cladding layer is 2 mm thick and the substrate is 3 mm thick.
[0059] Through observation and mechanical property testing, it can be concluded that the method of combining laser cladding and aging treatment can produce reinforced components with high surface hardness, wear resistance, high bonding strength with the substrate, and good core toughness.
[0060] This invention is not limited to the specific embodiments described above. The invention extends to any new feature or combination disclosed in this specification, as well as any new method or process step or combination disclosed herein.
Claims
1. A method for enhancing the surface wear resistance of low-carbon martensitic stainless steel components, characterized in that: For stainless steel substrates, the following steps are included: S1: Clean the stainless steel substrate surface and dry the wear-resistant alloy powder to be clad; the wear-resistant alloy powder consists of the following elements by mass percentage: C (0-0.03%); Cr (11.5%-14.0%); Ni (7.5%-9.5%); Cu (1.0%-2.5%); Nb (0.3%-0.6%); Ti (0.5%-1.4%); Mo (0.1%-0.3%); Mn (0.1%-0.3%); Si (0.1%-0.3%); Al (0.1%-0.3%); P (0-0.04%); S (0-0.03%); O (0-0.04%); N (0-0.04%); the remainder is Fe and unavoidable impurity elements; S2: Wear-resistant alloy powder is clad onto a stainless steel substrate using laser cladding to obtain a clad component; the wear-resistant alloy powder and the stainless steel substrate have similar C and Cr contents. S3: The obtained clad component is aged at a temperature below the initial temperature of austenite transformation (Ac1).
2. The method according to claim 1, characterized in that: The stainless steel matrix is 04Cr13Ni5Mo.
3. The method according to claim 1, characterized in that: In step S1, the oil stains are wiped off with alcohol when cleaning the stainless steel substrate surface.
4. The method according to claim 1, characterized in that: In step S2, the thickness of the cladding layer on the stainless steel substrate is between 2mm and 5mm.
5. The method according to claim 4, characterized in that: Multiple laser cladding processes are employed to achieve the desired cladding thickness.
6. The method according to claim 4, characterized in that: The particle size of the wear-resistant alloy powder is 150-300 mesh.
7. The method according to claim 1, characterized in that: In step S3, during the aging process, the temperature is 460℃~480℃, the time is 3h~4h, and the cooling method is air cooling.
8. A wear-resistant low-carbon martensitic stainless steel component, prepared using the method for enhancing the surface wear resistance of low-carbon martensitic stainless steel components as described in any one of claims 1-7, characterized in that: It includes a base layer and a cladding layer, wherein the cladding layer is located on the surface of the base layer.
9. The wear-resistant low-carbon martensitic stainless steel component according to claim 8, characterized in that: The thickness of the cladding layer is between 2mm and 5mm; and / or the material of the base layer is 04Cr13Ni5Mo.
Citation Information
Patent Citations
Solution aging treatment cavitation erosion resistant nickel-titanium alloy coating and preparation method thereof
CN118497740A
Preparation method for metal-doped modified turbine blade laser cladding surface coating layer
CN109778184A